(untitled) (Journal of Parents and Teachers, 2016)
This article describes some of the stressors present in the teaching work, as well as burnout syndrome and its opposite, work engagement, as the two main dimensions of teacher well-being. Finally, some coping strategies to promote this well-being are explained.